Forage quality of plant species consumed by capybaras (Hydrochoerus hydrochaeris) in the Paraná River Delta, Argentina - Corriale, Maria Jose (2011)
The capybara (Hydrochoerus hydrochaeris) is a selective herbivore that may show a preference for certain plant species. Such a preference is likely to be explained by the nutritional benefits hypothesis, stating that the nutritional value of species selected by capybaras is higher than that of avoided ones. Therefore, the objectives of this work are to evaluate the nutritional value of the plant species eaten by capybaras in the Lower Delta of the Paraná River, and to test the nutritional benefits hypothesis by analyzing forage quality. Samples of consumed plant species were collected from habitats located in the study area. We also collected plant species that are very abundant in the field but absent in the capybara's diet, some of which are consumed by other native herbivores such as coypus (Myocastor coypus). Their nutritional quality was analyzed by estimating the following variables: water content, ash percentage, percentage of organic matter, acid detergent fiber, nitrogen percentage, crude protein, and caloric energy. The protein to fiber ratio was calculated and the water content was determined. The species consumed and not consumed by capybaras had a similar nutritional composition for all the variables analyzed (P < 0.05). A similar result was observed when comparing within consumed species, except for the caloric energy content, which was significantly higher in species consumed in greater proportion than availability (P < 0.05). Water content was at its minimum in species consumed in greater proportion than availability, and at its maximum in unconsumed species. No significant differences were found between consumed Poaceae and the rest of the consumed plant species for any of the analyzed variables. Diet selection by capybaras in the studied area may only be partially related to nutritional quality, and there would be other factors involved in foraging, such as physiological mechanisms of the animal or chemical and structural characteristics of food.